Legal provision for protection against sexual harassment at workplace: A comparison - Ali, Juhary; Ng, Lee Peng; Ismail, Ida Rosnita (2001)
Sexual harassment is also referred as sexual blackmail (in France), unwanted intimacy (in Holland) and sexual molestation (in Italy). Recent report indicated that sexual harassment has been the most serious problem for working women in Europe.Sexual harassment takes many forms ranging from a mere verbal insult to a physical advance that is unwelcome and sexually in nature.It can also be a stalking or a bullying tactic.In Malaysia, although there is no sexual law exists, a person who has been sexually harassed could seek legal remedies under Malaysian criminal law.Section 354 and Section 509 of the Penal Code regarding sexual harassment provide some forms of remedy for the victims.The launching of Malaysian Code of Practice on the Prevention and Eradication of Sexual Harassment in the Workplace was launched on August 17, 1999.The main objective of the Code is to increase awareness among all levels of workers on sexual harassment so that they would not involve in such an offence.However such Code -a mere guidelines to both employers and employees- creates no legal obligation for those who choose not to implement and it has no binding effect.The problems on sexual harassment, although relatively new in Malaysia, existed prior to 1960s during which neither a term to describe nor legal remedy to address.The issues on sexual harassment was alarming within 40 years and according to ILO in 1992, 23 countries revealed that sexual harassment was a major problem in workplace known to women. It has been reported that thirty six countries have enacted specific legislation on sexual harassment in order to handle and prevent this contagious problem from spreading into the society.Against these background, this paper reveals selected sexual harassment cases and highlights the legal provision against sexual harassment at workplace among nine Asian countries.